Patterns and Functions of Mā in the Diwan of Hatim al-Ṭaʾi: A Syntactic-Semantic Study - Shamakhi, Aisha Qasim Ali (Arts for Linguistic & Literary Studies, 2025)
This research investigates the syntactic and semantic functions of the particle mā in the Diwan of Hatim al-Ṭaʾi, a leading pre-Islamic poet of the ḥujjah era, with a focus on its diverse patterns and roles in meaning construction. After a brief overview of the poet and his corpus, the study examines particle mā in its negative, infinitival, and pleonastic uses, and nominal mā in its relative, conditional, interrogative, and other forms, supported by applied analyses of selected verses. The findings reveal that this diversity not only enriches meaning and reinforces emphasis but also contributes to maintaining metrical balance in poetry. Furthermore, the study highlights Hatim’s distinctive use of the Ḥijazi mā functioning like laysa, showing a stylistic alternation between application and non-application, which reflects individual choice rather than strict conformity to a specific dialect. This nuanced treatment challenges conventional grammatical interpretations and underscores the flexibility of linguistic usage in early Arabic poetry, thereby offering a fresh perspective on the role of mā in shaping both meaning and poetic form.